Prospective memory errors in everyday life: does instruction matter?. Issue 2 (7th February 2020) - Haas, Maximilian; Zuber, Sascha; Kliegel, Matthias; Ballhausen, Nicola
ABSTRACT: Previous research on prospective memory (PM, the ability to remember executing an intention in the future) suggests that PM errors constitute the majority of all everyday memory errors in younger adults. However, no study so far has investigated this ratio from an ageing perspective, nor examined whether different instructions may influence PM error reporting. In the present study, 64 younger and 64 older adults completed a 5-day diary on PM, memory and cognition errors following different reporting instructions: participants had to either focus on (1) PM errors only, (2) any daily memory errors (prospective or retrospective) or (3) any kind of cognitive error. Error descriptions were coded into subcategories and analysed both quantitatively and qualitatively. Independently of given instructions, PM was the most frequent everyday error for both age groups. Overall, results confirm age differences for everyday PM (but not for retrospective memory and cognition), suggesting that everyday PM might be spared from age-related decline. From a qualitative point of view, there seem to be differences in the type of missed intentions, which correspond with existent theories of ageing. In conclusion, the present study allowed for a deeper insight into everyday PM functioning in younger and older adults.